Rab7—a novel redox target that modulates inflammatory pain processing. Issue 7 (July 2017) - Kallenborn-Gerhardt, Wiebke; Möser, Christine V.; Lorenz, Jana E.; Steger, Mirco; Heidler, Juliana; Scheving, Reynir; Petersen, Jonas; Kennel, Lea; Flauaus, Cathrin; Lu, Ruirui; Edinger, Aimee L.; Tegeder, Irmgard; et al.
Abstract : Abstract: Chronic pain is accompanied by production of reactive oxygen species (ROS) in various cells that are important for nociceptive processing. Recent data indicate that ROS can trigger specific redox-dependent signaling processes, but the molecular targets of ROS signaling in the nociceptive system remain largely elusive. Here, we performed a proteome screen for pain-dependent redox regulation using an OxICAT approach, thereby identifying the small GTPase Rab7 as a redox-modified target during inflammatory pain in mice. Prevention of Rab7 oxidation by replacement of the redox-sensing thiols modulates its GTPase activity. Immunofluorescence studies revealed Rab7 expression to be enriched in central terminals of sensory neurons. Knockout mice lacking Rab7 in sensory neurons showed normal responses to noxious thermal and mechanical stimuli; however, their pain behavior during inflammatory pain and in response to ROS donors was reduced. The data suggest that redox-dependent changes in Rab7 activity modulate inflammatory pain sensitivity. Abstract : Rab7 is a newly identified redox target in the nociceptive system. Mice deficient for Rab7 display reduced inflammatory and ROS-induced pain behavior.